Posthypertonic Lysis of Modified Erythrocytes in Citrate Medium - Olejnik, O. A.; Ramazanov, V. V.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2003)
Posthypertonic lysis (PHL) of erythrocytes under conditions of the absence of chloride anion entering flux at sodium citrate presence), as well as the effect of cytoskeletal modifiers on the erythrocyte posthypertonic sensitivity were investigated. It was demonstrated, that the erythrocyte sensitivity to PHL depended on the band 3 protein interaction with cytoskeleton, and the resistance did on the band 4.1 protein interaction with the membrane.